Impact of supraglottic device with assist ventilation under general anesthesia combined with nerve block in uniportal video-assisted thoracoscopic surgery - Xiang, Xiaobing; Zhou, Huidan; Wu, Yingli; Fang, Jun; Lian, Yanhong (Medicine (Baltimore), 2020)
With the improvement of anesthesia and surgical techniques, supraglottic device with assist ventilation under general anesthesia (GA) combined with nerve block is gradually applied to video-assisted thoracoscopic surgery. However, the safety of assist ventilation has not been fully confirmed, and a large number of samples should be studied in clinical exploration. The subjects included 120 patients, undergoing elective thoracoscopic GA, with American Society of Anesthesiologists (ASA) physical status I or II, were randomly divided into 3 groups, 40 cases in each group. Group T: received double-lumen bronchial intubation, Group I: received intercostal nerve block using a supraglottic device, Group P: received paravertebral nerve block using a supraglottic device. Mean arterial pressure, heart rate, saturation of pulse oximetry and surgical field satisfaction, general anesthetic dosage and recovery time were recorded before induction of GA (T0), at the start of the surgical procedure (T1), 15 minutes later (T2), 30 minutes later (T3), and before the end of the surgical procedure (T4). Static and dynamic pain rating (NRS) and Ramsay sedation score were recorded 2 hours after surgery (T5), 12 hours after surgery (T6), 24 hours after surgery (T7), time to get out of bed, hospitalization time and cost, patient satisfaction and adverse reactions. There was no significant difference with the surgical visual field of the 3 groups (P > .05). The MAP, HR and SpO2 of the 3 groups were decreased from T2 to T3 compared with T0(P < .05). Compared with group T: the total dosage of GA was reduced in group I and group P, the recovery time was shorter, the time to get out of bed was earlier (P < .05), the hospitalization time was shortened, the hospitalization cost was lower, and the patient satisfaction was higher (P < .05). The static and dynamic NRS scores were lower from T5 to T7 (P < .05). Ramsay sedation scores were higher (P < .05), and the incidence of adverse reactions was lower (P < .05). Comparison between group I and group P: Dynamic NRS score of group P was lower from T6 to T7 (P < .05). Supraglottic device with assist ventilation under general anesthesia combined with nerve block in uniportal video-assisted thoracoscopic surgery is safe and feasible.